2022
DOI: 10.1159/000524995
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fluoxetine to Reduce Weight in Adults with Overweight or Obesity: Abridged Republication of the Cochrane Systematic Review

Abstract: Introduction: Using fluoxetine is one of many weight-loss strategies. A serotonin reuptake inhibitor indicated for depression believed to impact weight control by changing an individual’s appetite; however, its benefit-risk ratio is unclear. The aim of this review is to assess the efficacy and safety of fluoxetine in reducing weight in adults with overweight or obesity. Methods: We searched Cochrane Library, MEDLINE, Embase and other databases without language restrictions. Cochrane Collaboration tool and GRAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…The multivariate analysis revealed markedly elevated risk of SAEs with concomitant administration of fluoxetine and anti-obesity agents. Although fluoxetine is not classified as anti-obesity agents, studies revealed modest weight reduction of 2.7kg with fluoxetine administration; thus, it is possible that some patients may be using fluoxetine for weight loss [ 44 ]. However, considering that obese populations are at elevated risk of depression, concomitant administration of fluoxetine may be more common than reported ADE cases.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analysis revealed markedly elevated risk of SAEs with concomitant administration of fluoxetine and anti-obesity agents. Although fluoxetine is not classified as anti-obesity agents, studies revealed modest weight reduction of 2.7kg with fluoxetine administration; thus, it is possible that some patients may be using fluoxetine for weight loss [ 44 ]. However, considering that obese populations are at elevated risk of depression, concomitant administration of fluoxetine may be more common than reported ADE cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research by Petersen et al [ 62 ] in BALB/c mice provided information that a 3-week supplementation of 10% of the diet with INU, FOS, XOS, GOS, apple pectin, polydextrose, or beta-glucan didn’t disturb the body weight of the tested animals. In turn, results from clinical trials showed, that FLU given chronically at a dose of 60 mg/day might have a modest effect on weight loss compared to a placebo in adults with overweight or obesity, although it may also induce many adverse events [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that obesity is associated with depression and less consistent evidence that depression is linked to obesity [ 108 ]. Among adults with overweight or obesity suffering from depression, fluoxetine showed a modest effect on weight loss as an anti-obesity medication by achieving weight loss of 2.7 kg and a decline in body mass index by 1.1 kg/m 2 compared with placebo, owing to the alleviation of hunger inhibition signals and thus reduced food intake [ 109 ]. However, further research is necessary to investigate the impact of this medication on weight loss in pediatrics.…”
Section: Treatmentmentioning
confidence: 99%